In vitro anti-canine distemper virus activity of fucoidan extracted from the brown alga Cladosiphon okamuranus - Trejo Ávila, Laura M.; Morales Martinez, M. E.; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth; Zapata Benavides, Pablo; Morán Santibáñez, Karla Selene; Rodríguez Padilla, Cristina (Springer, 2014)
Canine distemper virus (CDV) is a morbillivirus related to measles virus that infects dogs and other carnivores. CDV has a significant global impact on animal health; however, there is no current antiviral treatment for CDV infection. In recent years, it has been demonstrated that sulfated polysaccharides exhibit antiviral properties both in vivo and in vitro, despite their low cytotoxicity to host cells. Fucoidan is a sulfated polysaccharide found in the cell wall matrix of brown algae. In this study, we evaluated in vitro anti-CDV activity of fucoidan, which was derived from Cladosiphon okamuranus. Fucoidan actively inhibited CDV replication in Vero cells at a 50% inhibitory concentration (IC50) of 0.1 lg/ml. The derived selectivity index (SI50) was[20,000. This polysaccharide likely inhibits viral infection by interference in the early steps and by inhibiting CDV-mediated cell fusion. Fucoidan may be useful in development of pharmacological strategies to treat and control CDV infection.